The integral
∫
0
2
π
6
cos
(
x
)
−
1
0
d
x
=
A
π
.
Find the value of − A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I = ∫ 0 2 π 6 cos x − 1 0 d x Since the integrand is even = 2 ∫ 0 π 6 cos x − 1 0 d x Let t = tan ( 2 x ) ⟹ d t = 2 1 + t 2 d x ⟹ cos x = 1 + t 2 1 − t 2 = 2 ∫ 0 π 6 ( 1 + t 2 1 − t 2 ) − 1 0 d x = 2 ∫ 0 π 2 ( 3 − 3 t 2 − 5 − 5 t 2 ) ( 1 + t 2 ) d x = 2 ∫ 0 ∞ 2 + 8 t 2 − d t = − ∫ 0 ∞ 1 + 4 t 2 d t Let u = 2 t ⟹ d u = 2 d t = − 2 1 ∫ 0 ∞ 1 + u 2 d u = − 2 tan − 1 u ∣ ∣ ∣ ∣ 0 ∞ = − 2 1 × 2 π = − 4 π
⟹ − A = 4
dat was easy
does not deserve level4
Problem Loading...
Note Loading...
Set Loading...
This type of integral can be handled easily using contour integration. The substitution z = e i x converts the integral into one of a rational function of z around the unit circle, centre 0 , which is then equal to 2 π i times the sum of the residues of the integrand at singularities of modulus less than 1 . Thus ∫ 0 2 π 6 cos x − 1 0 1 d x = = = ∫ ∣ z ∣ = 1 3 z + 3 z − 1 − 1 0 1 i z d z = i 1 ∫ ∣ z ∣ = 1 3 z 2 − 1 0 z + 3 1 d z i 1 ∫ ∣ z ∣ = 1 ( 3 z − 1 ) ( z − 3 ) d z = 2 π R e s z = 3 1 ( 3 z − 1 ) ( z − 3 ) 1 3 ( 3 1 − 3 ) 2 π = − 4 1 π making the answer 4 .